Pragmatic Markers in the English-Language Election Discourse (on the Example of Speeches by Candidates for the Post of Leader of the Conservative Party of Great Britain) - O. V. Obvintseva; D. V. Pitolin; T. O. Obvintseva (Научный диалог)
The study of the pragmatic functions of such discourse elements as pragmatic markers, which are used in one of the genres of English-language political discourse - the pre-election speeches of candidates are presented in the article. The attention is paid in the article to the correlation of the concepts of “political discourse” and “pre-election discourse”, the features, functions and pragmatic settings of the genre of pre-election speeches are described, the terms pragmatic marker and discursive marker are defined. The material for the study was the video of the election speeches of candidates for the post of leader of the Conservative Party of Great Britain B. Johnson and J. Hunt, published on the YouTube online platform in June-July 2019. The classification of pragmatic markers by B. Fraser was chosen as the methodological basis of the study. As a result of the study, an inventory of pragmatic markers was compiled, used by candidates in several rounds of election campaigns, and the functions that pragmatic markers of various types perform in the genre of political discourse under study are described. The results of a comparative analysis of the use of pragmatic markers by each candidate in their pre-election speeches are presented. Conclusions are drawn about how, due to pragmatic markers, the arsenal of manipulative and influencing language means of election discourse is increasing.